Fabrication and application of natural clay ceramic membrane - Miss OUANID, Manal (My University, 2025)
With increasing water scarcity and pollution of natural sources, water treatment technologies have become essential to ensure access to clean and safe water. Membrane technology represents an effective and innovative solution for water purification and wastewater treatment, enabling efficient removal of contaminants. Although polymeric membranes are widely used, their limitations in corrosion and thermal resistance and short lifespan have driven researchers to explore ceramic membranes based on natural materials like clay. This research focuses on the preparation of ceramic membranes using locally sourced natural clay, investigating the impact of raw material composition, pore-forming agents, drying, and sintering temperatures on the physical and mechanical properties of the membranes. A mixture of clay, kaolin, starch, and sodium carbonate was used to produce membranes with high mechanical strength and appropriate porosity, ensuring effective filtration and sustainable performance. The study includes the steps of collecting and preparing raw materials, membrane shaping, drying, and sintering at various temperatures, while monitoring their influence on microstructure, mechanical strength, and permeability. This work contributes to the development of cost-effective and high-performance ceramic membranes from abundant natural resources, paving the way for their application in efficient and sustainable water and wastewater treatment. Keywords: ceramic membranes, natural clay, water treatment, wastewater treatment, membrane technology. ملخص: في ظم حزايذ َذسة انًيبِ وحهىد يصبدسهب، أصبحج حقُيبث يعبنجت انًيبِ يٍ انضشوسيبث األسبسيت نضًبٌ حىفيش ييبِ َقيت وصبنحت نالسخخذاو. حُعخبش حقُيت األغشيت يٍ انحهىل انفعبنت وانًبخكشة في يجبل حُقيت انًيبِ ويعبنجت ييبِ انصشف انصحي، حيذ حخيح فصم انًهىربث بكفبءة عبنيت. وعهى انشغى يٍ االَخشبس انىاسع نألغشيت انبىنيًيشيت، إال أٌ يحذوديخهب في يقبويت انخآكم وانحشاسة وقصش عًشهب انخشغيهي دفعج انببحزيٍ إنى حطىيش أغشيت خزفيت حعخًذ عهى يىاد طبيعيت يزم انطي.ٍ يشكز هزا انبحذ عهى ححضيش أغشيت خزفيت يٍ انطيٍ انطبيعي انًسخخشس يٍ يصبدس يحهيت، ودساست حؤريش حشكيبت انًىاد انخبو وعىايم حشكيم انًسبو ودسجبث حشاسة انخجفيف وانخهبيذ عهى انخصبئص انفيزيبئيت وانًيكبَيكيت نألغشيت. حى اسخخذاو خهيظ يٍ انطي،ٍ انكىني،ٍ انُشبء، وكشبىَبث انصىديىو نخحضيش أغشيت راث قىة ييكبَيكيت عبنيت ويسبييت يُبسبت حضًٍ كفبءة في انخششيح واسخذايت في األداء. حشًم انذساست يشاحم جًع وححضيش انًىاد انخبو، حشكيم األغشيت، انخجفيف، وانخهبيذ بذسجبث حشاسة يخخهفت يع يشاقبت حؤريشهب عهى انبُيت انًجهشيت، انقىة انًيكبَيكيت، وَفبريت األغشيت. هزا انبحذ يسبهى في حطىيش أغشيت خزفيت ب جذيذة السخخذايهب في يعبنجت انًيبِ يُخفضت انخكهفت وعبنيت األداء حعخًذ عهى يىاسد طبيعيت يخىفشة، يًب يفخح آفبقً وييبِ انصشف انبيئي بكفبءة واسخذايت. الكلمات المفتاحية : األغشيت انخزفيت، انطيٍ انطبيعي، يعبنجت انًيب،ِ يعبنجت ييبِ انصشف، حقُيت األغشيت. Résumé : Face à la raréfaction croissante des ressources en eau et à la pollution des sources naturelles, les technologies de traitement de l’eau sont devenues indispensables pour garantir l’accès à une eau propre et potable. La technologie membranaire constitue une solution efficace et innovante pour la purification de l’eau et le traitement des eaux usées, permettant une séparation efficiente des polluants. Bien que les membranes polymères soient largement utilisées, leurs limites en termes de résistance à la corrosion, à la chaleur et leur courte durée de vie ont poussé les chercheurs à développer des membranes céramiques à base de matériaux naturels tels que l’argile. Ce travail de recherche porte sur la fabrication de membranes céramiques à partir d’argile naturelle locale, en étudiant l’influence de la composition des matières premières, des agents formateurs de pores, ainsi que des températures de séchage et de frittage sur les propriétés physiques et mécaniques des membranes. Un mélange composé d’argile, de kaolin, d’amidon et de carbonate de sodium a été utilisé pour produire des membranes présentant une résistance mécanique élevée et une porosité adaptée garantissant une filtration efficace et durable. L’étude couvre les étapes de collecte et de préparation des matières premières, de mise en forme des membranes, de séchage et de frittage à différentes températures, avec une analyse de leur effet sur la microstructure, la résistance mécanique et la perméabilité. Ce travail contribue au développement de membranes céramiques performantes et à faible coût, à partir de ressources naturelles abondantes, ouvrant de nouvelles perspectives pour leur application dans le traitement durable et efficace de l’eau et des eaux usées. Mots-clés : membranes céramiques, argile naturelle, traitement de l’eau, traitement des eaux usées, technologie membranaire.
Keywords: ceramic membranes; natural clay; water treatment; wastewater treatment; membrane technology